Biomarkers in Advanced Heart Failure: Implications for Managing Patients With Mechanical Circulatory Support and Cardiac Transplantation. (July 2020) - Loungani, Rahul S.; Mentz, Robert J.; Agarwal, Richa; DeVore, Adam D.; Patel, Chetan B.; Rogers, Joseph G.; Russell, Stuart D.; Felker, G. Michael
Abstract : Biomarkers have a well-defined role in the diagnosis and management of chronic heart failure, but their role in patients with left ventricular assist devices and cardiac transplant is uncertain. In this review, we summarize the available literature in this patient population, with a focus on clinical application. Some ubiquitous biomarkers, for example, natriuretic peptides and cardiac troponin, may assist in the diagnosis of left ventricular assist device complications and transplant rejection. Novel biomarkers focused on specific pathological processes, such as left ventricular assist device thrombosis and profiling of leukocyte activation, continue to be developed and show promise in altering the management of the advanced heart failure patient. Few biomarkers at this time have been assessed with sufficient scrutiny to warrant broad, universal application, but encouraging limited data and large potential for impact should prompt ongoing investigation.